1523 - The first martyrs of the Reformation What has changed in the 500 years since the first martyrs of the Reformation? - Sinnaghel, Harry (ASP editions - Academic and Scientific Publishers, 2023)
1 July 1523, Hendrik Vos and Johan van den Esschen died by burning at the stake on the Grand-Place in Brussels. They were the first martyrs of the Reformation. Following this event, the Faculty of Protestant Theology and Religious Studies (FPTR) in Brussels organized a colloquium to discuss what has changed in the 500 years since the first martyrs of the Reformation. After an historical introduction to set the scene regarding 1 July 1523, this colloquium dealt with the consequences of the Reformation on various and diverse topics that include secularization, the role of women, democracy, virtue ethics, interreligious dialogue, ending with a proposal on how to move forward. This book can be a starting point for further scientific research, especially in the area of secularization, women's emancipation, and the beginning of the Jewish-Christian dialogue. I recommend this book to anyone interested in the Reformation and its consequences.